Cassava technology adoption: Constraints and opportunities - Henry, Guy; Gottret, María Verónica (International Center for Tropical Agriculture, 1995)
The impact of improved technological components depends to a large extent on the appropriateness of the intervention for the end-user, the efficiency of the technology transfer mechanism and the socio-economical and political conditions of the technology target area. In order to optimize impact the constraints in each of these areas of influence need to be analyzed and opportunities need to be identified to alleviate these constraints. From a different perspective these constraints can be divided into technical, institutional, socio-economical and political limitations. Technical constraints include the appropriateness of the technology intervention. Institutional constraints include the research /extension integration, technology transfer mechanism, seed multiplication capacity, and adoption information feed-back mechanism. The socio-economic constraints include the presence and capacity of commercial seed multiplication and distribution entities and the market situation regard ing possible price premiums or potential demand for additional supplies (as a consequence of the technology adoption). The political constraints may be adverse governmental policy interventions. The results from different adoption studies are used to demonstrate the importance of appropriate technologies, institutional support, transfer mechanism, and market influence. One case study treats the adoption and impact of cassava technologies within the Integrated Cassava Project in Colombia's north coast. The other study concerns the adoption of cassava variety Rayong 3 in Thailand. The last section of the paper identifies and discusses various opportunities that are open to research and extension institutions to alleviate adoption constraints and that subsequently can translate into higher impact.